2007
DOI: 10.1243/0954406jmes472
|View full text |Cite
|
Sign up to set email alerts
|

Micropower generation with microgasturbines: A challenge

Abstract: This paper describes the development of a microgasturbine with a rotor diameter of 20 mm. The target electrical power output lies around 1 kW. The total system fits in a cylinder with a diameter of 95 mm and a length of 120 mm. The system contains the same components as a large gasturbine generator: compressor, recuperator, combustion chamber, turbine, and electrical generator. Major challenges are the high rotational speed (500 000 r/min), high turbine inlet temperature (1200 K), and the efficiency of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…A number of materials have been proposed for micro gas turbines, ranging from steel alloys to ceramics such as silicon nitride or silicon carbide [4,41,31]. As heat transfer through the housing and shaft is found to be moderately influential for the baseline material selection, a trade-off study is performed for a range of materials, as shown in Table 1.…”
Section: Impact Of Materials Conductivitymentioning
confidence: 99%
“…A number of materials have been proposed for micro gas turbines, ranging from steel alloys to ceramics such as silicon nitride or silicon carbide [4,41,31]. As heat transfer through the housing and shaft is found to be moderately influential for the baseline material selection, a trade-off study is performed for a range of materials, as shown in Table 1.…”
Section: Impact Of Materials Conductivitymentioning
confidence: 99%
“…An exhaust diffuser is added to create a sub-ambient pressure at the turbine exit, such that more power can be extracted. Though certain problems are introduced due to this design comparing to the use of two separated shafts (a high-speed compressor shaft plus a low-speed generator shaft), the single shaft design is still preferable due to its simplicity (Peirs et al 2007). …”
Section: General Layoutmentioning
confidence: 99%
“…But the physics and mechanics influencing the design of the components do change with scale, so that the optimal detailed designs can be quite different (Peirs et al 2007). The main difference between a small and large gas turbine is the amount of fluid submitted to an almost unchanged thermodynamic cycle.…”
Section: Thermodynamic Cycle and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…An example of application of such bearings are the smart electrospindles for very high speed [1][2][3], in which the spindle must be supported in stable conditions up to 200-250 krpm [4]. Other application sectors are micro-turbomachines [5] and movable electric appliances [6].…”
Section: Introductionmentioning
confidence: 99%